Assessment of patient safety culture in primary health care in Muscat, Oman: a questionnaire -based survey - Muna Habib AL Lawati; Stephanie D. Short; Nadia Noor Abdulhadi; Sathiya Murthi Panchatcharam; Sarah Dennis (BMC Family Practice, 2019)
Abstract Background Patient safety is a universal issue which affects countries at all stages of health system development. Patient safety research in primary care reveals that globally millions of people suffer disabilities, injuries, or death due to unsafe medical practices. This study aims to explore the understanding of frontline primary health care professionals regarding patient safety culture in health care facilities in Oman. Methods A questionnaire–based survey was conducted using a validated Hospital Survey of Patient Safety Culture tool. Invitations were sent to all 198 health professionals from each occupational category from each primary care center in Muscat, Oman. Results The total number of respondents was 186 participants out of 198 (response rate: 94%). Overall, the staff had a strong sense of teamwork within the units (85%), they reported organization learning for continuous improvement (84%) and teamwork across the units (82%). However, the four dimensions which received the lowest scores were related to communication problems between the staff (23%), non-punitive response to errors (27%), frequency of event reporting (40%), and errors occurring when transferring patients to higher levels of health care during handoffs and transitions (46%). Conclusions Overall, the participants rated patient safety in the primary health care setting as excellent or very good and the perception of patient safety was moderately positive. The core areas of strength were teamwork within the units with positivity and organization learning and continuous improvement. The weaknesses were non-punitive response to errors, inadequate staffing and hand offs and transition. The results of this study will provide policy makers and health care professionals with a detailed understanding of the current patient safety culture in primary care in Muscat, Oman. The results will be used by the Ministry of Health to inform policy and strategies to strengthen patient safety within primary health care in Oman.